2001
DOI: 10.1016/s0377-1237(01)80006-x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging in Intracranial Tuberculosis

Abstract: Tuberculosis (TB) is still a major cause of serious illness in many parts of the world. Intracranially, TB manifests itself variably as meningitis, tuberculoma and tubercular abscess [II. Although its appearance on MR is not absolutely specific, it is important in the proper clinical setting to recognize the range of possible patterns that can be observed on images £2]. Magnetic Resonance Imaging (MRI) has emerged as a quality imaging tool aiding in the diagnostic evaluation of intracranial TB variably display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…The mortality in tuberculous meningitis remains exceptionally high. Clinical response to anti-tubercular treatment in all forms of CNS tuberculosis is contingent on an early diagnosis before irreversible neurological deficit occurs; therefore, the management strategy should involve an early diagnosis coupled with aggressive treatment [ 11 , 12 ]. The culture from the CSF analysis confirmed tuberculous infection 3 weeks later.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality in tuberculous meningitis remains exceptionally high. Clinical response to anti-tubercular treatment in all forms of CNS tuberculosis is contingent on an early diagnosis before irreversible neurological deficit occurs; therefore, the management strategy should involve an early diagnosis coupled with aggressive treatment [ 11 , 12 ]. The culture from the CSF analysis confirmed tuberculous infection 3 weeks later.…”
Section: Discussionmentioning
confidence: 99%
“…On CT scan, they appear as dural based variably enhancing lesion with or I. Berete et al Open Journal of Modern Neurosurgery without calcification, and often associated with active communicative hydrocephalus [12]. MRI is the investigation of choice and usually shows a hypointense lesion on T1 weighted, and a hypointense lesion with surrounding hyperintense edema on T2-weighted and enhances well with gadolinium contrast [4] [13]. In our case the lesion was multifocally infiltrating the brain parenchyma, and the enhancement pattern was heterogenous, but the dural insertion, the calcifications, the edema and the hydrocephalus were present.…”
Section: Discussionmentioning
confidence: 99%
“…In each subtype, small tubercular lesions known as Rich foci initially develop in the CNS, either in the meninges, brain, or spinal cord, and become active after a quiescent period (1,2) via distant hematogenous spread with low-level bacteremia (2). The imaging findings of parenchymal miliary tuberculomas have been described in only a few case reports and research articles (1,(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), published mostly from developing countries. It has been reported that intraparenchymal tuberculomas occur in the frontal and parietal lobes in adults, in contrast to the infratentorial region in children (10).…”
Section: Discussionmentioning
confidence: 99%